2023
DOI: 10.1186/s10194-023-01574-5
|View full text |Cite
|
Sign up to set email alerts
|

PAR2 activation in the dura causes acute behavioral responses and priming to glyceryl trinitrate in a mouse migraine model

Abstract: Background Migraine is a severely debilitating disorder that affects millions of people worldwide. Studies have indicated that activation of protease-activated receptor-2 (PAR2) in the dura mater causes headache responses in preclinical models. It is also well known that vasodilators such as nitric oxide (NO) donors can trigger migraine attacks in migraine patients but not controls. In the current study we examined whether activation of PAR2 in the dura causes priming to the NO donor glyceryl t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Fig 8B).Consistent with the expression of EphB2 in most subsets of DRG neurons in humans[69], we observed that ephrin-B2-Fc treatment increased p-eIF4E in both large diameter neurons greater than40 μm diameter (Fig 8C) as well as in small diameter neurons (<40μm; Fig 8D).…”
supporting
confidence: 84%
“…Fig 8B).Consistent with the expression of EphB2 in most subsets of DRG neurons in humans[69], we observed that ephrin-B2-Fc treatment increased p-eIF4E in both large diameter neurons greater than40 μm diameter (Fig 8C) as well as in small diameter neurons (<40μm; Fig 8D).…”
supporting
confidence: 84%
“…These interventions aim to modulate molecular targets associated with migraine pathogenesis, highlighting the potential of diverse treatment modalities. Studies utilize different animal models of migraine induction, including NTG-induced models ( 57 , 62 , 68 , 71 ), GTN-induced models ( 31 , 73 ), and others. Variations in animal species, strains, and induction methods contribute to the diversity of findings and insights into migraine mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, behavioral responses to the endogenous protease neutrophil elastase, which can cleave and activate Par2, were assessed. Dural neutrophil elastase induced both acute responses and priming to GTN in WT mice, whereas Par2KO mice displayed no such responses [ 100 ].…”
Section: Introductionmentioning
confidence: 99%